Molecular biomarker testing for non-small cell lung cancer: consensus statement of the Korean Cardiopulmonary Pathology Study Group - Sunhee Chang; Hyo Sup Shim; Tae Jung Kim; Yoon-La Choi; Wan Seop Kim; Dong Hoon Shin; Lucia Kim; Heae Surng Park; Geon Kook Lee; Chang Hun Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Molecular biomarker testing is the standard of care for non-small cell lung cancer (NSCLC) patients. In 2017, the Korean Cardiopulmonary Pathology Study Group and the Korean Molecular Pathology Study Group co-published a molecular testing guideline which contained almost all known genetic changes that aid in treatment decisions or predict prognosis in patients with NSCLC. Since then there have been significant changes in targeted therapies as well as molecular testing including newly approved targeted drugs and liquid biopsy. In order to reflect these changes, the Korean Cardiopulmonary Pathology Study Group developed a consensus statement on molecular biomarker testing. This consensus statement was crafted to provide guidance on what genes should be tested, as well as methodology, samples, patient selection, reporting and quality control.